Development of an interactive biosensing application for assessing finger dexterity - Abrahami, Michal Greenberg; Warszawer, Yehuda; Kalron, Alon; Shirbint, Emanuel; Didikin, Maria; Achiron, Anat (Digital health, 2025)
Accurate finger function assessment is crucial for monitoring the performance of daily hand activities. However, specialized digital applications are lacking for evaluating various finger tasks. This study aims to develop a custom digital biosensing application to assess finger dexterity. We developed a digital biosensing application compatible with smartphones and tablets that enables 3-min testing of finger dexterity, measuring velocity and accuracy for each finger and each movement orientation. Data were collected for the dominant hand from a large cohort of healthy volunteers to establish population norms values. The construction of the application involved a comprehensive, multi-stage process designed to ensure functionality, user-friendliness, and cross-platform compatibility using the Flutter framework by Google with specific adaptations for Android and iOS. To evaluate the application and construct population norms, 318 healthy subjects, 197 females and 121 males, mean ± age 37.7 ± 13.5 years, were tested. Velocity was faster for the vertical and horizontal tests than all other tests and fastest for finger 2, while the pinch test was the slowest for all fingers. Deviation from any required test orientation was more evident for the circle test and mainly for finger 5, while the vertical and horizontal orientations were the most unerring. Analysis of finger dexterity by age disclosed better performance in the younger age group (<35 years); no effect of gender for both velocity and deviation was observed. The developed digital application allows immediate evaluation of finger dexterity. The established population norms can provide a comparative standard for assessing patients with disorders like multiple sclerosis, sensory neuropathy, or stroke.